2002
DOI: 10.1093/emboj/21.9.2282
|View full text |Cite
|
Sign up to set email alerts
|

Directional bias during mating type switching in Saccharomyces is independent of chromosomal architecture

Abstract: Haploid Saccharomyces cells have the remarkable potential to change mating type as often as every generation, a process accomplished by an intrachromosomal gene conversion between an expressor locus MAT and one of two repositories of mating type information, HML or HMR. The particular locus selected as donor is dictated by the mating type of the cell, a bias that ensures productive mating type interconversion. Here we use green¯uorescent protein tagging of the expressor and donor loci on chromosome III to show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
2
23
2
Order By: Relevance
“…Determination of the Average Spatial Distance between MAT and HMR-The spatial distance between MATa and HMR has been analyzed in a cells (36). These authors introduced Lac repressor binding sites at the MATa locus and Tet repressor binding sites at the HMR locus in a strain expressing GFP-LacI and GFP-TetR fusion proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Determination of the Average Spatial Distance between MAT and HMR-The spatial distance between MATa and HMR has been analyzed in a cells (36). These authors introduced Lac repressor binding sites at the MATa locus and Tet repressor binding sites at the HMR locus in a strain expressing GFP-LacI and GFP-TetR fusion proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless this occurs in HO ϩ yeast cells once per cell cycle with remarkable fidelity. Previous studies have tried without success to identify mating-type-specific spatial clues that predispose one HM locus and not the other to interact with the cleaved MAT locus (4,49). Although neither found matingtype-specific juxtaposition, it was argued that Chr3L has a distinct mobility in MATa versus MAT␣ cells, which might favor exchange with MATa (4).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was proposed that the preference of MATa for HML␣ could be achieved by a cell-type-specific subnuclear juxtaposition of the relevant loci. To test this, Simon et al (49) examined the spatial relationship between the HM loci and MAT by fluorescently tagging pairs of loci in diploid cells in which one allele of the active MAT was deleted. They found that the relative positions of the three mating type loci are identical in MATa and MAT␣ cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Donor choice has been studied for mating-type switching in the yeast Saccharomyces cerevisiae where DSBs at MAT initiate conversion that depends on interactions with linked homologous sequences located on opposite arms of the chromosome. Donor choice in this highly specialized system involves a recombination enhancer sequence that regulates recombination across an entire chromosome arm (21), although the physical proximity of donor and recipient loci also plays a role (33,63). A more general case of mitotic DSB-induced gene conversion in yeast was examined by Inbar and Kupiec (25) in which a broken allele could be repaired from either of two ectopic loci on heterologous chromosomes.…”
mentioning
confidence: 99%